EFEKTIVITAS KEBIJAKAN PENGGUNAAN DANA DESA DALAM PEMBERDAYAAN MASYARAKAT DI NAGARI KOTA RANTANG TAHUN 2021-2022 DITINJAU DARI PERSPEKTIF FIQIH SIYASAH - soraya oktarina; Sri Anggia (FisiPublik: Jurnal Ilmu Sosial dan Politik, 2024)
ommunity empowerment is an important task and program for every Nagari government. In Nagari Koto Rantang, the quality of community empowerment is still a concern for the nagari government due to the high school dropout rate, low levels of community human resources, and the lack of active community participation in nagari management. The solution to handle increasing community empowerment programs is to issue appropriate policies and allocate nagari funds. This research uses a combined method of field research with a qualitative approach through observation and interviews. The aim of the research is to see to what extent the nagari fund policy is effective in creating empowerment for the community in Nagari Koto Rantang. The results of the research show that the determination of the policy on the use of village funds in the Koto Rantang village is going quite well. However, community empowerment has not yet become the nagari's main priority because the Koto Rantang nagari prioritizes physical nagari development. Apart from that, community empowerment programs are still experiencing obstacles due to the lack of activity of nagari organizations and difficulties in distributing funds during the Covid-19 era. There are various problems that hinder the effectiveness of community empowerment funding policies, ranging from time, cost, to accuracy of use. In siyasah fiqh, leaders must be responsible for the benefit of all their people, including in terms of community empowerment. In this case, the Koto Rantang government has implemented the concept of leadership according to Islamic concepts, although implementation still presents obstacles.